Can Augmented Reality Revive Vocabulary Learning? A Study on Motivation Among Secondary EFL Learners - Fithrotul 'Aini, Alfi; Tarihoran, Naf'an; Kheryadi (Universitas Hamzanwadi, 2025)
Augmented Reality (AR) is increasingly seen as a powerful educational tool that provides immersive and interactive learning experiences. However, its influence on English vocabulary learning among secondary school students remains underexplored. This study examines the effectiveness of AR in improving English vocabulary mastery and learning motivation among Grade VII students in Serang City, Indonesia. Using a randomized mixed-methods approach, 75 students (aged 12–13) were divided into an experimental group (n = 38), which received AR-based vocabulary instruction, and a control group (n = 37), which was taught using traditional image-based media. Quantitative data were collected through pre- and post-tests of vocabulary skills and motivation questionnaires, both showing high reliability (α = 0.932 and α = 0.890, respectively). Qualitative data were gathered via semi-structured interviews and analyzed thematically. Results from the Mann-Whitney U test and independent samples t-test indicated a significant improvement in vocabulary learning and motivation among students exposed to AR. The experimental group performed better than the control group in satisfaction, engagement, and interest. Interview results further supported these findings, emphasizing AR’s ability to increase interactivity, support memory retention, cater to diverse learning styles, and boost overall learner enthusiasm. These results highlight the pedagogical potential of AR in fostering vocabulary development and motivation in secondary English education.